Effects of sewage water on diatoms (Bacillariophyceae) and water quality in two tropical streams in Costa Rica - Michels, Astrid (Revista de Biología Tropical, 1998)
The influence of pig farm sewage on waler quality and diatoms was studied in two tropical streams over a five-month period. Sewage water inflows led to increased concentrations of soluble reactive phosphorus. ammonium, nitrite and to oxygen deficits. Due to self-purification, a decrease of ammonium coupled with an increase in nitrate occurred downstream. In total, 127 species of diatoms were recorded. Thirteen species restricted to tropical regions were found particularly at the spring-site. Correlation between dominant species and hydro-chemical parameters were calculated: Nitzshiq fonticola occurred especially at unpolluted sites, Gomphonema parvulum, Navicula subminuscula and Nitzschia palea were more abundant at sewage-polluted sites and Cocconeis placentula seemed to be tolerant to pollution. A cluster-analysis showed that diatom assemblages at the spring-site were different from all other sites. Light and water current were discussed as factors influencing the spring-site assemblages.